2023
DOI: 10.1001/jamaneurol.2023.3889
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Slow-Wave Sleep Loss and Incident Dementia

Jayandra J. Himali,
Andree-Ann Baril,
Marina G. Cavuoto
et al.

Abstract: ImportanceSlow-wave sleep (SWS) supports the aging brain in many ways, including facilitating the glymphatic clearance of proteins that aggregate in Alzheimer disease. However, the role of SWS in the development of dementia remains equivocal.ObjectiveTo determine whether SWS loss with aging is associated with the risk of incident dementia and examine whether Alzheimer disease genetic risk or hippocampal volumes suggestive of early neurodegeneration were associated with SWS loss.Design, Setting, and Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Besides cardiovascular diseases, Alzheimer's disease represents another aging disease with shared risk factors that are associated with changes in sleep [43][44][45] . Recent studies underscore the crucial role of sleep, particularly NREM sleep, in facilitating the removal of metabolic waste from the brain through the glymphatic system 46,47 .…”
Section: Cortico-cardiovascular Coupling Likely Deteriorates In Neuro...mentioning
confidence: 99%
“…Besides cardiovascular diseases, Alzheimer's disease represents another aging disease with shared risk factors that are associated with changes in sleep [43][44][45] . Recent studies underscore the crucial role of sleep, particularly NREM sleep, in facilitating the removal of metabolic waste from the brain through the glymphatic system 46,47 .…”
Section: Cortico-cardiovascular Coupling Likely Deteriorates In Neuro...mentioning
confidence: 99%
“…We agree that the association between sleep and dementia could be bidirectional, and this is something we have discussed here and elsewhere. 1,2,4 Our comprehensive analysis represents an important step in understanding the relationship between irregular sleep and dementia with replication and extension in other cohorts needed.…”
mentioning
confidence: 98%
“…Thus, reduced N3 as a predictor of future NDD is also consistent with the hypothesis that initial brainstem involvement of NDD produces an early prodrome of reduced SWS. A recent report from the Framingham Heart Study showed that in participants who completed PSGs over two timepoints, in the time periods 1995–1998 and 2001–2003, the decline in SWS across this interval predicted development of all causes of dementia in the subsequent 17 years [ 26 ]. Finally, there is less data pertaining to REM sleep and it is less clear that this stage is relevant to the glymphatic hypothesis.…”
mentioning
confidence: 99%